Mathematical modeling of dehydration resistance of pericarp tissues and endosperm in fruits of arabic coffee - Dias, Camila de Almeida; de Andrade, Ednilton Tavares; Lemos, Isabella Ávila; Borém, Flavio Meira; Westerich, Diogo Nogueira; da Silva, Ana Claudia Almeida (Coffee Science - ISSN 1984-3909, 2020)
Coffee represents an important source of income for producers and for the Brazilian economy, being the second product in the country’s agricultural exports. Unlike other agricultural products, freshly harvested coffee has a high fruit water content, approximately 60% (dry base). It is fundamental to optimize the drying process for cost reduction and quality maintenance, making it necessary to understand the interdependence relation of the tissues of the pericarp and the coffee endosperm during the dehydration of the fruit. The objective of this work was to elaborate a drying model for the constituent parts of coffee fruits evaluating the resistance of each of the pericarp tissues and endosperm. The experiment was set up in a 4x6 factorial scheme (4 relative humidity of the drying air and natural, pulped natural coffee, pericarp tissues and endosperm: 1 - natural coffee and 2 – pulped natural coffee, 3 - exocarp + a portion of mesocarp, 4 - mesocarp, 5 - endocarp, 6 - endosperm]) in a completely randomized design with four replicates. The results were analyzed through analysis of variance and regression, using the statistical software STATISTICA 5.0®. The resistance to water outflow, regardless of the processing or the fruit part of the coffee, is greater when the coffee is dried with the lowest relative humidity. The natural coffee was the treatment that presented greater resistance, while the lower resistance was presented by the exocarp + a portion of mesocarp.